Sexual Risk Behaviors Among Women with Bipolar Disorders - Marengo, Eliana (2015)
The aim of this study was to investigate sexual health and sexual risk behaviors for sexually transmitted infections (STI) among women with bipolar disorder (BDW). Sixty-three euthymic women diagnosed with bipolar disorder type I, II or not otherwise specified were included and matched with a control group of 63 healthy women. Demographic and clinical data, structured sexual health measures and extensive assessment of sexual risk behavior were obtained and compared between groups. BDW had casual partners, were in non-monogamous sexual partnerships and had sex with partners with unknown HIV condition more frequently than healthy control women. History of two or more STI was more frequent among BDW. Inclusion of sexual behavior risk assessment among BDW in treatment is necessary to better identify those women with higher risk for STI and to take measures to improve their sexual health.